Active Corrosion Protection by Epoxy Coating on Li2CO3-Pretreated Anodized Aluminum Alloy 2024-T3 - Minhas, Badar; Dino, Sahib; Huang, Luyao; Wu, Dequan (Frontiers in Materials, 2022)
The fast leaching and robust barrier property of inhibitors are the basic fundamentals for the formation of active protective coatings to protect aluminum alloys. Herein we developed an active protective surface based on an epoxy coating and an underlying lithium carbonate (Li2CO3) treated anodized aluminum alloy 2024-T3. The morphology of the Li-LDH layer was studied to know its formation mechanism. The electrochemical studies revealed that the fast and adequate leaching of lithium led to a substantial increment of corrosion resistance of the scratched coating in 3.5 wt% NaCl from 1 to 8 days. Time of flight secondary ion mass spectroscopy (ToF-SIMS) results indicated that Li was distributed in the lateral direction and covered the scratched area. The 3D images indicated that different lithium compounds were formed and 90% of the scratched area covered with the lithium protective layer over immersion time. A combined approach of morphology observations, electrochemical measurements and ToF-SIMS showed the lithium protective layer offered good corrosion resistance. On the contrary, lithium provided fast and adequate leaching from the coating, demonstrating the good active protection for aluminum and its alloys.